Download presentation
Presentation is loading. Please wait.
1
Solving Linear Equations
Elimination S. Calahan
2
x + 2y = 5 -x + y = 13 Example Eliminate the x since the
co-efficients are opposites.
3
x + 2y = 5 -x + y = 13 3y = 18
4
3y = 18 y = 6
5
Use one of the original equations to substitute y =6. x + 2y = 5
y = 6, so find x Use one of the original equations to substitute y =6. x + 2y = 5 x + 2(6) = 5 x + 12 = 5
6
x + 12 = 5 x + 12 = 5 Solve = -12 x = - 7 Since y = 6 and x = -7, then the solution is (-7, 6)
7
Solve the system of equations.
2x – 6y = 6 2x + 3y = 24 Notice the x co-efficients are the same.
8
Subtract the equations 2x – 6y = 6 - (2x + 3y = 24)
Distribute the negative
9
Now add 2x – 6y = 6 -2x - 3y = -24 -9y = - 18 y = 2
10
Using one of the 2 equations solve for x
2x – 6y = 6 Remember y = 2 So, 2x – 6(2) = 6 2x – 12 = 6 2x = 18
11
2x – 12 = 6 2x = 18 x = 9
12
So the solution is (9, 2)
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.